Unpredictability, Transformation, and the Pedagogical Encounter: Reflections on "What Is Effective" in Education. Issue 3 (26th June 2013) - O'Donnell, Aislinn
Abstract In this article, Aislinn O'Donnell offers a set of reflections on the relation between therapy and education. In the first section, she examines criticisms of therapeutic education, mobilizing the example of prison education to highlight the difficulties that arise from imposing prescriptive modes of subjectification and socialization in pedagogy. In the second section, she addresses the relation between therapy and education by focusing on just one element of the experience of education: those moments at which a subject has the potential of becoming significant in the life of a student. An important dimension of the educator's authority involves noticing such moments, fostering the conditions that make them more likely, and engaging in the creative process and practice of deciding how best pedagogically to respond to these moments. In the third section, O'Donnell develops this idea by detailing a philosophical approach and practice that understands "effectiveness" in education as bound to practice, creative responsiveness, and the judgment of the educator in concrete, singular pedagogical situations, rather than construed in terms of generic models of "best practice."